Kloṅ chen sñiṅ gi thig le las Gcod yul mkhaʼ ʼgroʼi gad rgyaṅs źes bya ba bźugs so - ʼJigs-med-gliṅ-pa Raṅ-byuṅ-rdo-rje, 1729 or 30-1798 (s.n., 1970)
Esoteric instruction on the Gcod practices of Tibetan Lamaism; from the Kloṅ chen sñiṅ thig visions (dag snaṅ) of ʼJigs-med-gliṅ-pa.